2018
DOI: 10.11607/ijp.5628
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Proof-of-Principle Bite Force Study of Two Experimental Denture Adhesives and a Commercially Available Adhesive

Abstract: Only adhesive 1 was significantly better than the negative control, and its performance did not match that of the positive control. Adhesives 1 and 2 showed the largest number of oral adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…The clinically relevant difference detectable was 2.30 lbs for area over baseline between 0 and 12 hr (AOB 0–12 ), using two‐sided t tests with a 5% significance level, assuming a residual standard deviation (SD; square root of within mean square error) of 2.83 lbs. The estimate of residual SD was obtained as the higher of the observed variability from two previous bite force studies (Jose et al, ; Data on file).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinically relevant difference detectable was 2.30 lbs for area over baseline between 0 and 12 hr (AOB 0–12 ), using two‐sided t tests with a 5% significance level, assuming a residual standard deviation (SD; square root of within mean square error) of 2.83 lbs. The estimate of residual SD was obtained as the higher of the observed variability from two previous bite force studies (Jose et al, ; Data on file).…”
Section: Methodsmentioning
confidence: 99%
“…No further significance testing would be performed if the initial validation step was not achieved. The reason for this validation step was to ensure that the study methodology had been performed as expected, the superior performance of the Reference adhesive over No adhesive having been demonstrated previously (Jose et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, no statistically significant difference was observed between the marketed reference adhesive and no adhesive for AOB 0–12 . This was unexpected given the results of previous studies of similar design that found that the reference adhesive used here demonstrated statistically significantly greater incisal bite force until dislodgement compared with no adhesive (Jose et al, ). In the current study, the mean AOB 0–12 values were 1.39 with no adhesive and 2.07 with the reference adhesive.…”
Section: Discussionmentioning
confidence: 51%
“…In the current study, the mean AOB 0–12 values were 1.39 with no adhesive and 2.07 with the reference adhesive. In previous studies, mean AOB 0–12 with no adhesive was slightly higher at around 2.15, whereas mean AOB 0–12 with the reference adhesive was much higher, at around 4.79 (Burnett et al, ; Jose et al, ).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation